Формування математичної моделі організаційно-технічного методу скорочення негативних наслідків надзвичайних ситуацій медико-біологічного характеру місцевого рівня поширення - Шевченко, Роман Іванович (НТУ "ХПІ", 2017)
В роботі розглянуто процес формування математичної моделі організаційно-технічного методу скорочення негативних наслідків надзвичайних ситуацій медико-біологічного характеру. В ході якого проведена формалізація параметрів та формування низки припущень, що дозволило визначити еквіваленту схему інформаційно-комунікативного взаємовпливу процесів поширення негативних наслідків НС МБ характеру та розробити відповідну трьохфакторну імітаційну математичну модель залежності кількості загиблих та числа жертв у наслідок НС МБ характеру міського рівня.

The paper considers the process of forming a mathematical model of organizational and technical method for reducing the negative consequences of emergency situations of medical and biological character. In the course of which the formalization of parameters and the formation of a number of assumptions were made, which allowed to determine the equivalent of the scheme of information and communication interaction of the processes of spreading the negative consequences of emergency situations of medical and biological character and to develop an appropriate three-factor simulation mathematical model of the dependence of the number of victims and the number of victims as a result of emergency situations of medical and biological the character of the urban level.
Formation of the mathematical model of the organizational and technical method of reducing the negative consequences of emergency situations of the medical and biological character of the local level of distribution
Keywords: модель математична; допомога гуманітарна; небезпека; emergencies; medical hazard; biological hazard